2005
DOI: 10.7773/cm.v31i12.84
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization of sediment cores from the continental shelf off the western rias area (NW Iberian Peninsula)

Abstract: The present work aims to understand the origin of sediments deposited in the Galician coastal zone and continental shelf. Selected sediment cores were studied using different geochemical approaches: grain-size measurements, carbonate determinations and elemental analyses. Chemical analyses were carried out by multielemental techniques: energy dispersive X-ray fluorescence spectrometry (EDXRF) and instrumental neutron activation analysis (INAA). The grain-size distribution demonstrated that samples collected of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Ba excess is commonly used as a tool for the reconstruction of paleoproductivity although some authors have discussed its validity (e.g., Anderson and Winckler 2005). In core high (Araújo et al, 2002;Corredeira et al, 2005). Two strong peaks are observed around 2000 cal.…”
Section: Discussionmentioning
confidence: 99%
“…Ba excess is commonly used as a tool for the reconstruction of paleoproductivity although some authors have discussed its validity (e.g., Anderson and Winckler 2005). In core high (Araújo et al, 2002;Corredeira et al, 2005). Two strong peaks are observed around 2000 cal.…”
Section: Discussionmentioning
confidence: 99%
“…However, in spite of the heavy metal contamination detected in the downstream region of some of the rivers draining the NW coastal area, including the Ave and the Duero rivers (the major source of fine-grained shelf sediments), no significant metal enrichments were detected in shelf sediments (Araújo et al 1998(Araújo et al , 2002Corredeira et al 2005Corredeira et al , 2009Mil-Homens et al 2006). However, in spite of the heavy metal contamination detected in the downstream region of some of the rivers draining the NW coastal area, including the Ave and the Duero rivers (the major source of fine-grained shelf sediments), no significant metal enrichments were detected in shelf sediments (Araújo et al 1998(Araújo et al , 2002Corredeira et al 2005Corredeira et al , 2009Mil-Homens et al 2006).…”
Section: Environmental Quality Of Seabed Sedimentsmentioning
confidence: 99%
“…However, in spite of the heavy metal contamination detected in the downstream region of some of the rivers draining the NW coastal area, including the Ave and the Duero rivers (the major source of fine-grained shelf sediments), no significant metal enrichments were detected in shelf sediments (Araújo et al 1998(Araújo et al , 2002Corredeira et al 2005Corredeira et al , 2009Mil-Homens et al 2006). Rubio et al 2000;Corredeira et al 2005Corredeira et al , 2009Á lvarez-Iglesias et al 2006;Á lvarez-Iglesias & Rubio 2009b;Rubio et al 2010) but they are confined to only the uppermost layers of the cores, representing about half of the last century. Both factors depend on the textural and compositional variability of the different sediment types present in the study area.…”
Section: Environmental Quality Of Seabed Sedimentsmentioning
confidence: 99%
“…Pepelnik et al 264 showed that despite biogenous decalcification one year later, which led to increased organic matter, the concentrations of Bi, Cd and W in 2002 and 2003 sediment samples were still higher than those measured in 1998. A Spanish language paper 265 reported XRF and INAA data to assist in the geochemical characterisation of sediment cores from the continental shelf off the north-western Iberian Peninsula. The down-core profiles showed evidence of recent contamination by As and Zn, although there was no evidence of exportation to the adjacent continental shelf.…”
Section: Geological and Industrial Mineralsmentioning
confidence: 99%